Bis{2-bromo-4-chloro-6-[2-(phenyl-sulfon-yl)hydrazonometh-yl]phenolato-κN,O}copper(II) - Yusnita, Juahir; Ali, Hapipah Mohd; Puvaneswary, Subramaniam; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The Cu atom in the title compound, [Cu(C(13)H(9)BrClN(2)O(3)S)(2)], is chelated by two deprotonated Schiff base ligands in a square-planar coordination geometry; the Cu atom lies on a center of inversion. The -NH- group of one anion forms an intra-molecular hydrogen bond to the phenolate atom of the symmetry-related ion.